Exploring Teachers’ and Students’ Attitudes on Non-Formal Online English Learning: A Case Study from EYL Papua Students (Conference on English Language Teaching, 2025)
This study investigates the perceptions of teachers and students regarding the use of virtual classrooms to support English as a Foreign Language (EFL) proficiency, particularly among young learners in Papua. It aims to identify both the benefits and challenges of online learning in a non-formal education context that offers a fully digital learning environment. The research involved two teachers and two students, with data gathered through one-on-one, semi-structured interviews. A qualitative descriptive approach was used to analyze the participants’ responses. The results reveal generally positive attitudes from both teachers and students toward virtual classrooms as effective tools for facilitating the teaching and learning of English. However, the study also highlights significant obstacles, particularly related to unstable internet connections and limited access to appropriate digital devices. These technical difficulties posed challenges for both parties in maintaining smooth interaction and instructional flow. Despite these setbacks, the study underscores the potential of virtual classrooms in enhancing English language education in remote areas like Papua. By examining key components such as technology use, instructional methods, teaching media, and assessment strategies, the research offers valuable insights for educators and policymakers seeking to improve the quality and accessibility of online English instruction. It also emphasizes the importance of fostering digital literacy as part of broader educational development efforts in under-resourced regions.